2004
DOI: 10.1007/978-3-540-28649-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Analysis of Two Model-Based Vehicle Tracking Approaches

Abstract: Abstract. An experimental comparison of 'Edge-Element Association (EEA) ' and 'Marginalized Contour (MCo)' approaches for 3D modelbased vehicle tracking in traffic scenes is complicated by the different shape and motion models with which they have been implemented originally. It is shown that the steering-angle motion model originally associated with EEA allows more robust tracking than the angular-velocity motion model originally associated with MCo. Details of the shape models can also make a difference, dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…-OFThresh (see item 'Optical Flow Thresholding' in Section 3). -Wheelarch, the addition of wheelarches as already studied with a smaller sample size in Dahlkamp et al (2004b). -Shadow, the addition of visible shadow edges to the model.…”
Section: Experiments Settingmentioning
confidence: 98%
“…-OFThresh (see item 'Optical Flow Thresholding' in Section 3). -Wheelarch, the addition of wheelarches as already studied with a smaller sample size in Dahlkamp et al (2004b). -Shadow, the addition of visible shadow edges to the model.…”
Section: Experiments Settingmentioning
confidence: 98%
“…The objective is to find this template back in each image considered, (Ballard, 1981;Ferryman et al, 1995;Tan et al, 1998;Pece and Worrall, 2002;Hinz, 2003;Zhao and Nevatia, 2003;Dahlkamp et al, 2004;Pece, 2006;Ottlik and Nagel, 2008). The disadvantage of model-based methods is the high dependency on geometric details of the considered object, which in our case would require that vehicles should appear in the image sequence with many details and with clear boundaries.…”
Section: Related Workmentioning
confidence: 99%
“…As said in (Dahlkamp et al, 2004(Dahlkamp et al, , 2007, switching from 2D tracking in the image plane to 3D tracking in the scene domain often results in a substantially reduced failure rate, because more prior knowledge about the objects can be utilized. For example, foreground regions are not always homogeneous, and we need some criteria to merge regions that are likely to belong to the same object.…”
Section: Introductionmentioning
confidence: 99%
“…(Dahlkamp et al, 2004) showed how a shadow added to their polyhedral model could improve the accuracy when fitting the model to edge features. (Song and Nevatia, 2007) give examples of how simulating shadows on a 3D box (with fixed size) can improve detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation